Differential Effects of GABA(B) Autoreceptor Activation on Ethanol Potentiation of Local and Lateral Paracapsular GABAergic Synapses in the Rat Basolateral Amygdala - Silberman, Yuval (2009)
Many studies have demonstrated that GABAergic inhibition within the basolateral amygdala (BLA) plays an integral role in the regulation of anxiety, an important behavioral component in the etiology of alcoholism. Although ethanol has recently been shown to enhance BLA GABAergic inhibition via two distinct populations of inhibitory cells, local and lateral paracapsular (lpcs) interneurons, little is known about the mechanisms underlying ethanol potentiation of these two inhibitory pathways. Ethanol is known to enhance GABAergic inhibition in many brain regions via a complex array of pre- and postsynaptic mechanisms. In addition, ethanol’s presynaptic effects are often subject to GABA(B) autoreceptor (GABA(B)-R) modulation. Therefore, in this study, we characterized GABA(B)-R function and modulation of ethanol actions at local and lpcs GABAergic synapses. At local synapses, we found significant paired-pulse depression (PPD, 250 msec interpulse interval) which was abated by SCH-50911 (GABA(B)-R antagonist). No significant PPD was detected at lpcs synapses, but SCH-50911 significantly potentiated lpcs-evoked IPSCs. Baclofen (GABA(B)-R agonist) had similar depressant effects on local- and lpcs-evoked IPSCs, however baclofen pretreatment only reduced ethanol potentiation at local synapses. Ethanol also significantly enhanced the frequency of spontaneous and miniature IPSCs, and these effects were also sensitive to GABA(B)-R modulators. Collectively, these data suggest that stimulus-independent inhibitory responses recorded from BLA principal neurons primarily reflect the activity of local GABAergic interneurons and provide additional evidence that ethanol potentiates local BLA inhibitory synapses primarily via a presynaptic enhancement of GABA release that is tightly regulated by GABA(B)-R. In contrast, ethanol potentiation of lpcs GABAergic synapses is not sensitive to GABA(B)-R activation and does not appear to involve increased presynaptic GABA release.